Abundance and diversity of the fecal resistome in small-holder broiler systems in Kenya - Njaramba, Jane K.; Antonissen, G.; Muloi, Dishon; Ochieng, Linnet; Ibayi, Eugine L.; Moodley, Arshnee (Wiley, 2023)
Poultry production is expected to increase in Kenya by 375% from 35 million birds in 2012 to 166 million birds by 2050. This intensification is posited to lead to increased antibiotic use which is a major driver of antimicrobial resistance (AMR). Antibiotics are commonly used in Kenya to treat infections, without prior diagnostic tests, for prophylaxis and as growth promoters. AMR studies tend to focus on bacterial isolation and the determination of specific AMR phenotypes and genotypes. This narrow approach only characterizes a very limited proportion of the circulating resistome as bacteria exist as communities, where interspecies interactions play a role in the dissemination of AMR genes (ARGs). This study aims to apply a culture-independent method to characterize the diversity and relative abundance of the resistome in small-holder broiler farms (200–2000 birds) and investigate any associations between ARG abundance and diversity and farming/production practices. We hypothesize that resistome is not affected by farm demographic and production practices. To test this hypothesis, genomic DNA extracted from composite fecal samples collected from 129 broiler farms in three peri-urban counties will be analyzed using the SmartChip™ Real-Time PCR system by Resistomap Oy (Helsinki, Finland). Ecological models and ordination methods will be implored to predict and analyze variation in ARG diversity and composition by demographic and production parameters. This study will provide novel information on the breath of ARGs circulating in small holder broiler production systems and identify potential ARG farm profiles that can be used to better inform the design of interventions to decrease the development and spread of AMR from broiler farms.